Humidity Control Strategies for Solid-State Fermentation: Capillary Water Supply by Water-Retention Materials and Negative-Pressure Auto-controlled Irrigation - He, Qin; Peng, Huadong; Sheng, Mengyao; Hu, Shishan; Qiu, Jiguo; Gu, Jiayu (Frontiers in Bioengineering and Biotechnology, 2019)
Solid-state fermentation (SSF) has regained interest owing to its advantages in solid waste treatment and fermentation industries. However, heterogeneous heat and mass transfer are often caused by the absence of free water and noticeable water loss from microbial utilization and moisture evaporation in SSF. It is necessary to explore more effective ways to solve issues of water loss and water supplement in SSF based on online capillary water monitoring because capillary water is the dominant form of water that is present and lost in substrate. Two novel capillary-water supply strategies were proposed, established and evaluated using three selected reference strains, including water-retention materials and negative-pressure auto-controlled irrigation (NPACI). This study employed superabsorbent polymer, a kind of water-retention materials to enhance enzyme productivity with the most significant increase of 2.47 times. Moreover, the combination of NPACI and 0.1% superabsorbent polymers increased productivity by 2.80-fold, together with lowered gradients of temperature, moisture and products. Furthermore, a modified liquid-supply SSF was constructed through successful capillary water control by proposed humidity control strategies. This modified SSF system could address the shortcomings of inhomogeneous culture of traditional SSF.